1996
DOI: 10.1111/j.1365-2044.1996.tb07859.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of epidural infusions of fentanyl or pethidine with bupivacaine in the management of postoperative pain

Abstract: Summary A double-blind randomised clinical trial was undertaken in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Pethidine has also been given by continuous epidural infusion in combination with local anaesthetic. Pethidine 1.5 mg/ml plus bupivacaine 0.06% infused at rates up to 20 ml/h provided good analgesia after aortic surgery that was comparable to that achieved with fentanyl 4 µg/ml plus bupivacaine 0.06% 43 .…”
Section: Continuous Epidural Infusionmentioning
confidence: 78%
“…Pethidine has also been given by continuous epidural infusion in combination with local anaesthetic. Pethidine 1.5 mg/ml plus bupivacaine 0.06% infused at rates up to 20 ml/h provided good analgesia after aortic surgery that was comparable to that achieved with fentanyl 4 µg/ml plus bupivacaine 0.06% 43 .…”
Section: Continuous Epidural Infusionmentioning
confidence: 78%
“…Previous studies [ 14 16 ] compared the analgesic efficacy of epidural meperdine and fentanyl with nearly similar finding to the present study, Paech, [ 14 ] compared the epidural meperdine or fentanyl during caesarean section and concluded that the quality of analgesia and duration of effective analgesia was good in both groups with minimum side effects. Cox et al, [ 15 ] compared epidural fentanyl and meperdine with bupivacaine in the management of postoperative pain after major abdominal surgery. Postoperative pain scores using a visual analogue scale were not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our experience multiple clinical studies were performed evaluating the value of epidural meperdine and demonstrated comparable effects to this study; Baraka et al, [ 17 ] demonstrated that epidural meperidine was associated with stable hemodynamics, satisfactory analgesia and reduced the need for administration of rescue analgesics when administered epidurally for obstetric patients. Cardiac output and mean arterial pressure was increased after epidural injection of meperidine [ 15 ].…”
Section: Discussionmentioning
confidence: 99%